Deployment and Evaluation of ChromeOS - Tamayo, Josan D.; Reyes, Angelo M.; Andrada, Emil Jayson; Amores, Setiel Marie; Garcia, Jemelyn O. (Future Science / FSH-PH Publications, 2024)
This paper aims to deploy the Google ChromeFlex Operating System and evaluate its efficiency. It uses a deep learning algorithm that analyzes all results from other users with the same browser type and on the same OS. This provides a meaningful evaluation of the computer unit's stressed components, including CPU, GPU, Memory, and Storage. Findings reveal that ChromeFlex OS works efficiently when the computer is connected online. Furthermore, GPU performance in ChromeFlex OS is lower in applications requiring graphics-related work like effects and videos. Using ChromeFlex OS on computer units used for daily tasks using Internet-based applications is recommended. ChromeFlex OS is a new operating system with limited compatibility, and most productivity tools compatible with old operating systems, such as Windows OS, MAC OS, and LINUX, among others, will not run in ChromeFlex OS.